Does Board Diversity Leadership affect corporate decisions and risk control? Evidence from Kenyan Commercial Banks - Kiweu, Josephat Mboya (My University, 2012)
The aim of this paper is to provide preliminary analysis of the relationship between corporate decisions, risk taking behavior and gender diversity. Using a panel of 28 Kenyan banks over the period 2000-2009, the study examined effect of corporate leadership in banks (number of female directors, proportion of female directors on boardrooms and gender presence in boards) and its value to board effectiveness, strategic control and monitoring of management. After controlling for relevant sources of endogeneity, the value of women in bank boardrooms could not be clearly justified. Particularly, the results show a negative association between profitability and female directors on the board and that diverse board in Kenyan banks probably lack decision control or are less effective. The study also shows that in the context of an emerging country, there is increased gender diversity in boards with women holding 9% of bank board seats in 2009. Larger boards and larger firms in addition to a long history of existence determine women appointment to the board. The study also finds evidence of a high risk appetite for a women director that does not pay off. In addition, the results support a positive association between gender diversity and financing costs. Overall, the results indicate tokenism is a key practice in the Kenyan banking sector.